Agriculture Studentsâ Ability to Write Past Tense at Taman Siswa University of Padang - Hayati, Amal (AT-TALIM, 2017)
The purpose of this research is to describe the third semester agriculture studentsâ ability to write simple sentences using simple past tense at Taman Siswa University Padang. This research was limited in three sentence forms; affirmative, negative and interrogative. Descriptive research was used in this study where the population was the third semester agriculture students at Taman Siswa University of Padang. The total number of the sample was 63 students. The finding showed that the ability of the third semester agriculture students of Taman Siswa University of Padang to write simple sentences using simple past tense was moderate. It could be seen that 70.97% students have moderate ability. In detail the percentages of each of form sentence were; 64.52% have moderate ability to write simple sentences in simple past tense of (verbal) affirmative, 74.20% have moderate ability to write simple sentences in simple past tense of (verbal) negative sentences, and 77.42% have moderate ability to write simple sentences in simple past tense of (verbal) interrogative sentences. Based on the research finding, it is suggested to the teachers to give more explanation about past tense and explain the usage of mechanics.Â  The students are suggested to learn more about past tense and use mechanics correctly.